The relationship between periodontal diseases and the risk of preeclampsia in pregnant women - Negin Rezavand; Mastaneh Kamravamanesh; Masoumeh Eyvazi; Jila Manouchehri; Maryam Hemati; Rozhin Feali; Mansour Rezaei (Mashhad University of Medical Sciences, 2021)
Introduction: Since periodontal disease is associated with chronic inflammation, it can be assumed that patients with periodontal disease have a higher risk of developing preeclampsia. Therefore, this study was performed with aim to determine the relationship between periodontal diseases and the risk of preeclampsia in pregnant women.  Methods: This case-control study was conducted in 2017-2019 on 100 pregnant women referred to Kermanshah Imam Reza Hospital in two groups of case (preeclamptic women) and control (normal pregnancy). The questionnaire was completed for each patient based on the required information including demographic information, periodontal parameters including bleeding on probing, plaque index, clinical attachment level, probing pocket depth. Data were analyzed using SPSS statistical software (version 20) and Mann-Whitney U and Student's t-tests. P<0.05 was considered statistically significant. Results: The study of periodontal indicators showed that there was no significant difference between the two groups in terms of bleeding on probing (P = 0.329), probing pocket depth index (P> 0.05) and clinical attachment level (P = 0.733). Only the plaque index was significantly lower in mothers with preeclampsia than mothers with normal pregnancies (P = 0.007).  Conclusion: Although no significant relationship was found between preeclampsia and maternal periodontal disease parameters, however, it is recommended that screening and prevention of periodontal disease in prenatal care be considered in order to improve maternal oral health and improve pregnancy outcomes through inter-professional collaboration.